FACTORS ASSOCIATED WITH THE INDICATION FOR CESAREAN SECTION IN FULL-TERM PRIMIPAROUS WOMEN AT THAI NGUYEN A HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: The study was conducted to evaluate several factors related to the indication for cesarean section among full-term primiparous women at the Obstetrics Department of A Thai Nguyen Hospital.Method: This was a descriptive cross-sectional and retrospective study based on 704 medical records of full-term primiparous women from September 1, 2024, to December 31, 2024.Results: The cesarean section rate among primiparous women was 56.1%. Specifically, the cesarean section rate was 55.7% in women under 35 years old and 70.6% in those over 35 years old. Regarding fetal weight, the cesarean section rate was 53.1% in the group weighing less than 3500g, and 68% in the group weighing more than 3500g. Maternal height showed an inverse correlation with the cesarean section rate, with a regression coefficient of -0.0607. The cesarean section rate was 54.7% among women with spontaneous conception and 79.5% among those with assisted reproductive conception.Conclusion: Statistical analysis indicated that factors significantly associated with the indication for cesarean section included fetal weight of 3500g or more (OR = 0.532; p = 0.001), maternal height (significant inverse correlation, p < 0.05), and conception through assisted reproductive techniques (OR = 3.2; p = 0.002). Additionally, the rate of cesarean section tended to increase with maternal age.
Keywords: Benign primipara, cesarean section, full-term, related factors, Thai Nguyen.